Evaluation of Clinical Competencies and Feedback of Senior Dental Students with Objective Structured Clinical Examination (OSCE) - Maryam Basirat; Fatemeh Rahbar Masouleh; Mehran Falahchai; Abtin Heidarzadeh (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: The Objective Structured Clinical Examination (OSCE) serves as a scientific evaluation method that effectively enhances clinical assessment techniques and transforms management strategies to solve educational problems. The aim of this study was to evaluate the clinical competency and feedback of senior dental students in Guilan province using the OSCE method. Methods: In this cross-sectional analytical study, 32 senior dental students of Guilan university of Medical Sciences participated in 2024. The data collection tools included questions from the National Clinical Competency Exam of Iran and a feedback questionnaire for students, utilizing the Craig-Patrick Model. Data analysis was conducted using IBM SPSS Statistics software version 26, employing Pearson correlation, Mann-Whitney, Chi-square, and Fisher's exact tests. P-value > 0.05 was considered statistically significant. Results: The mean age of the students was 25.55 (SD=3.60) years, and 53.1% were male. The mean GPA of the students surveyed was 16.82 (SD=0.59) out of 20.  The mean total score on the clinical competency exam was 75.12(SD=6.73) out of 100. The highest score was achieved in oral health, while the lowest score was in oral pathology. The test scores in oral surgery (P=0.016) and preclinical restorative courses (P=0.021) were significantly higher in women than in men. No significant correlation was found between the total exam score and student feedback scores (P=0.795). Only 20% of the students had positive feedback regarding this exam. Conclusion: The average clinical competency score of senior dental students in Guilan was at a good level; however, the students’ feedback regarding the exam was weak. Therefore, there is a need to prepare the necessary infrastructure in terms of facilities, educational environment, human resources, and financial support to enhance the clinical competencies of graduates.